A THEORY OF DEFLATION: CAN EXPECTATIONS BE INFLUENCED BY A CENTRAL BANK? - HARASHIMA, Taiji (Theoretical and Practical Research in Economic Fields; Vol 7 No 2 (2016): TPREF, Volume VII, Issue 2(14), Winter 2016DO - 10.14505/tpref.v7.2(14).02, 2016)
This paper examines how to reverse deflation to inflation. Once deflation takes root, it is not easy to reverse because of the zero lower bound in nominal interest rates. My model indicates that there are two steady states where both inflation/deflation (i.e., changes in prices) and real activity (i.e., quantities) remain unchanged: that is, there are inflationary and deflationary steady states. The model indicates that, to switch a deflationary steady state to an inflationary steady state, a central bank needs to influence the time preference rates of the government and the representative household. It is not easy, however, to do so, and the best way of switching deflation to inflation may be to wait for a lucky event (i.e., an exogenous shock).